Nd:YAG laser posterior capsulotomy performed under general anesthesia in the sitting position: a novel approach - Ely, Amanda; Pantanelli, Seth; Borkhetaria, Rucha; Barbieri, Carolyn; McQuillan, Patrick (Digital Journal of Ophthalmology, 2023)
We present a novel approach for performing an Nd:YAG laser posterior capsulotomy under general anesthesia with the patent in a seated position. We illustrate this approach in 2 cases, a young child and an adult patient with developmental delay. This technique may facilitate YAG capsulotomy in patients who cannot sit for the procedure.